Penataan Ruang Kawasan Nagari dalam Rangka Mengoptimalkan Pariwisata di Propinsi Sumatera Barat - Zahara, Zahara; Mirwati, Yulia; Hijriya, Shafira (Dinasti Review Publisher, 2024)
Regional development is an effort to utilize all regional potential to support development activities. Regional potential is the basic capital for the development of a community in improving its welfare. The existence of regional potential is a means that supports various development activities, both in terms of infrastructure potential, natural potential, population potential and business potential of the population as well as the potential of integrated cultural areas that can be exploited and used to improve development results in the context of justice and equity. area. A developed and developing regional area is strongly supported by regional potential. Regional territory is a geographical condition of an area that provides various opportunities for a region to manage regional potentials within a region. Community business activities also include the potential of productive areas in contributing to development activities and their results. The existence of sources of livelihood and employment owned by a community in a region will make a major contribution to development activities, especially in economic sectors that have the potential to increase a region's ability to become independent. Based on the description above, it becomes a concrete reference that every spatial planning activity carried out by the West Sumatra Regional Government, both in the Pariangan district of Tanah Datar Regency, the Harau district of Lima Puluh Kota District and the South Tiku District of Agam Regency have prepared spatial planning in order to increase tourism but not working as it should. This is due to the lack of clear coordination between nagari, tourism and spatial planning offices in order to increase tourism.